The role of the German and Italian constitutional courts in the rise of EU human rights jurisprudence: A response to Delledonne & Fabbrini - William Phelan (Trinity College Dublin, The University of Dublin, Trinity Research in Social Sciences (TRiSS), 2020)
The widespreadunderstandingthat the ECJ'searly fundamental rights jurisprudence in Internationale Handelsgesellschaft (1970) and other cases was developed in response to judgments of theGerman and Italian Constitutional Courts has recently been questioned.Delledonne and Fabbriniclaimboth that the conventional account ischronologically inaccurate -the European Court's famous fundamental rights decisions came beforethose of the German and Italian courts -and that it relies on an understanding ofpostwarhuman rights leadershipby these national constitutional courts which a closer look at theiractual record does not support.This paper demonstrates however that there is substantially more evidence that the Court of Justice was responding to the concerns of the German and Italian constitutional courts than is frequently set out by either critics or supporters of the more conventional approach. The Court of Justice's famous fundamental rights decisions did indeed comeafterthis issue had been first highlightedin judgments ofthe German and Italianconstitutionalcourts; thethreat to the uniform application of European law posed by the fundamental rights aspect of thesejudgments wasprominently notedin the writings ofECJ judges;andthe caution shownby the German and Italian constitutional courtsin reviewing postwar domestic legislation on human rights groundsis not in conflict with an active rolein promoting the ECJ's new human rights jurisprudence. In short therefore,there isconsiderableevidence that the ECJ was motivated to create its new human rights jurisprudence by the possible threatto the uniform applicationof European law posed by theGerman and Italianconstitutional courts.
Keywords: 330; European Court of Justice; German Constitutional Court; Italian Constitutional Court; Human Rights; European Law; Robert Lecourt